è¥¿åŠ å¤ç”¸æ±‰è¯æ•™å¸ˆä½¿ç”¨åæ—é‡Šå—çš„è°ƒæŸ¥ç ”ç©¶ - Marwan, .; Thamrin, Lily; ., Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
æ‘˜è¦ï¼šæœ¬æ–‡ç›®çš„æ˜¯è¿›ä¸€æ¥äº†è§£è¥¿åŠ å¤ç”¸æ±‰è¯æ•™å¸ˆä½¿ç”¨åæ—çš„æƒ…å†µå’Œæ•™å¸ˆå¯¹åæ—çš„çœ‹æ³•ã€‚é€šè¿‡ä½¿ç”¨é—®å·è°ƒæŸ¥æ³•æ”¶é›†æ•°æ®ï¼Œç„¶åŽç»Ÿè®¡åŠè¿›è¡Œåˆ†æžã€‚è°ƒæŸ¥åˆ†æžç»“æžœè™½ç„¶è¥¿åŠ å¤ç”¸æ±‰è¯æ•™å¸ˆéƒ½è®¤ä¸ºåæ—åœ¨å¦ç”Ÿçš„å¦ä¹ å…·æœ‰éžå¸¸é‡è¦çš„ä½œç”¨ï¼Œä½†åœ¨æ•™å¦å®žè·µæ—¶å¤§éƒ¨åˆ†æ•™å¸ˆé€‰æ‹©ä¸ç”¨åæ—è§£é‡Šæ±‰å—ã€‚è¿™è¡¨ç¤ºè¥¿åŠ æ±‰è¯æ•™å¸ˆå¯¹åæ—çš„æ„è¯†å’Œä½¿ç”¨è¿˜æ¯”è¾ƒå¼±ã€‚ä»Žåæ—æµ‹è¯•ç»“æžœä¹Ÿæ˜¾ç¤ºæ•™å¸ˆå¯¹åæ—çš„äº†è§£è¿˜ç›¸å¯¹æ¯”è¾ƒä½Žï¼Œä¸èƒ½å®Œå…¨äº†è§£åæ—çš„å«ä¹‰ã€‚ å…³é”®è¯ï¼šè¥¿åŠ å¤ç”¸ï¼Œæ±‰è¯æ•™å¸ˆï¼Œåæ— Abstract: The main purpose of this paper is want to learn more about the West Kalimantan Pontianak Mandarin teachers views and usage about the radical. This survey used questionnaires to collect the data, and then analyzed the data. After the survey and analyze of the data, author realized although West Kalimantan Pontianak Mandarin teachers are considered radical has a very important role in students learning process, but in teaching practice most of the teacher rather not to choose radical for teaching mandarin character, this means the awareness andÂ  practice of radical is still weak. The radical test results also show teachers about radical understanding is relatively low, canâ€™t fully understand the meaning of the radical. Keywords: West Kalimantan, Mandarin Teacher, Radical